An investigation into defect reduction techniques for growth of non‐polar GaN on sapphire. Issue 3 (17th February 2014) - Sutherland, Danny; Oehler, Fabrice; Zhu, Tongtong; Griffiths, James T.; Badcock, Thomas J.; Dawson, Philip; Emery, Robert M.; Kappers, Menno J.; Humphreys, Colin J.; Oliver, Rachel A.
Abstract: In this paper we describe the implementation and the characterisation of five different in‐situ defect reduction techniques for non‐polar ( a ‐plane) GaN growth on r ‐plane sapphire. Sample 1 (3D/2D) employs a methodology frequently applied on the c ‐plane, involving a low temperature nucleation layer (LTNL) followed by 3D GaN island formation and lateral coalescence. For Sample 2 (d3D) GaN islands are grown directly onto the sapphire with no LTNL, followed by lateral growth. Sample 3 (d3D Si) follows a similar procedure, but with high silicon doping in order to adjust the 3D GaN island shape. Sample 4 (SiNx ) utilises a silicon nitride interlayer between a LTNL and subsequent growth of a GaN layer. Sample 5 is grown by epitaxial lateral overgrowth (ELOG) coupled with a SiNx interlayer. X‐ray diffraction, scanning electron microscopy and cathodoluminescence are used to identify defects, and determined the threading defect density to vary from 1 x 10 10 –1 x 10 9 cm –2 and basal‐plane stacking fault (BSF) density to vary from 5 x 10 5 – 5 x 10 3 cm ‐1 . The improvement in crystal quality is reflected in the photoluminescence spectra by a comparison of the ratio of the GaN near band edge (NBE) emission to the BSF associated emission. It was determined that the ELOG method was most successful in blocking BSFs, with a density reduction of 2 orders of magnitude resulting in a fifteen‐fold increase in the NBE:BSF emission ratio increase. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)